2007
DOI: 10.1037/0278-6133.26.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which childhood personality traits influence adult health status: Educational attainment and healthy behaviors.

Abstract: The model extends past associations found between personality traits and health behaviors or health status by identifying a life-course pathway based on the health behavior model through which early childhood traits influence adult health status. The additional direct effects of personality traits indicate that health behavior mechanisms may not provide a complete account of relations between personality and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
230
4
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(252 citation statements)
references
References 33 publications
16
230
4
2
Order By: Relevance
“…2004, Hampson et al . 2006, 2007). Potentially, this knowledge could enable health professionals and those working in breastfeeding support to provide more targeted support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2004, Hampson et al . 2006, 2007). Potentially, this knowledge could enable health professionals and those working in breastfeeding support to provide more targeted support.…”
Section: Discussionmentioning
confidence: 99%
“…2006) and eating patterns (Hampson et al . 2007). Personality has also been shown to be related to several personal characteristics such as self‐efficacy, confidence and locus of control, which can in turn effect health outcomes (Vollrath 2001, Schaefer et al .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively consistent findings that Conscientiousness and Agreeableness are associated with the more frequent practice of health-promoting behaviors (e.g., Hampson et al, 2007), and Neuroticism is associated with fewer health-promoting behaviors (e.g., BoothKewley & Vickers, 1994), the reasons for these linkages are not well understood. In the current study, we address this gap by applying a self-regulatory perspective to the relation between these personality traits and health-promoting behaviors, using the SRRM (Sirois, 2015a(Sirois, , 2015b as our conceptual lens.…”
Section: The Present Researchmentioning
confidence: 97%
“…The Big Five trait taxonomy (Costa & McCrae, 1985;John & Srivastava, 1999) is one commonly used model for understanding how personality relates to health behaviors, with considerable evidence supporting the role of three particular personality factors. Both Conscientiousness and Agreeableness have been linked to the practice of health promoting behaviors (Booth-Kewley & Vickers, 1994;Hampson, Goldberg, Vogt, & Dubanoski, 2007;Ingledew & Brunning, 1999;Lemos-Giraldez & Fidalgo-Aliste, 1997), whereas Neuroticism is associated with fewer health promoting behaviors (Booth-Kewley & Vickers, 1994;Ingledew & Brunning, 1999). However, the reasons proposed for these relations have focused more on the qualities associated with these traits than on the underlying self-regulation processes that may be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that personality traits such as neuroticism, extraversion, anger, and hostility are significant predictors of mortality, and clinical health outcomes (Almada et al 1991;Wilson et al 2005;Hozawa et al 2006;Shipley et al 2007). Particularly in elderly populations, it has been hypothesized that these traits may affect subsequent physical health outcomes and mortality (Duberstein et al 2003;Wilson et al 2005;Krueger et al 2006;Hampson et al 2007). However, there have been few prospective studies of the association between personality traits and functional decline, and no studies have examined the risk factors related to loss of higher-level functional capacity.…”
Section: Introductionmentioning
confidence: 99%